2016
DOI: 10.1093/molbev/msw025
|View full text |Cite
|
Sign up to set email alerts
|

RhesusBase PopGateway: Genome-Wide Population Genetics Atlas in Rhesus Macaque

Abstract: Although population genetics studies have significantly accelerated the evolutionary and functional interrogations of genes and regulations, limited polymorphism data are available for rhesus macaque, the model animal closely related to human. Here, we report the first genome-wide effort to identify and visualize the population genetics profile in rhesus macaque. On the basis of the whole-genome sequencing of 31 independent macaque animals, we profiled a comprehensive polymorphism map with 46,146,548 sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
(22 reference statements)
3
30
0
Order By: Relevance
“…Combined with our data, 9 of the 26 captive Chinese RMs reported by Zhong et al. [ 7 ] were found to cluster with M. m. littoralis , 16 with M. m. lasiotis , and 1 with M. m. mulatta (Fig. 4d ).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Combined with our data, 9 of the 26 captive Chinese RMs reported by Zhong et al. [ 7 ] were found to cluster with M. m. littoralis , 16 with M. m. lasiotis , and 1 with M. m. mulatta (Fig. 4d ).…”
Section: Resultssupporting
confidence: 86%
“…(d) NJ tree including the 81 Chinese RMs derived from this study. The 26 captive Chinese RMs from Zhong et al [ 7 ] are indicated by blue dot.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A couple of research labs including ourselves demonstrated that rhesus monkeys spontaneously developed obesity with aging, metabolic syndrome (MetS), and diabetes [ 18 , 19 ]. Furthermore, the whole genome of rhesus macaque is available and better annotated now [ 15 , 20 22 ]. However, naturally occurring NAFLD has not been evaluated and reported in rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%